Implementasi Pendidikan Agama Islam Berbasis Al-Quran Dan Sunnah Menurut Pemahaman Salafus Shalih - Arif Usman; Fiqqi Assidieq Bahresy; Wahyu Rizky Romadhon; Afrizon Afrizon; Syaiful Anam; Jumadi Jumadi (An-Nuha, 2026)
This study aims to analyze the implementation of Islamic Religious Education (PAI) based on the Quran and Sunnah according to the understanding of Salafus Shalih at Pondok Pesantren Ihya' As-Sunnah Singkut, Jambi. In the midst of modern educational challenges, the Salafiyah model offers a return to the purity of Islamic teachings (Tasfiyah) and authentic upbringing (Tarbiyah). This research uses a qualitative descriptive case study approach with data collected through learning observations, in-depth interviews with administrators and teachers (Ustadz), and curriculum documentation. The findings show that: (1) The curriculum integrates the National and Pesantren Curriculum with emphasis on Aqidah Tauhid, Tahfidz Al-Quran, and Arabic; (2) Learning methods prioritize talaqqi, memorization, and practicing sunnah; (3) Educational orientation places Adab (manners) before Ilm (knowledge). The implication is the formation of students with strong religious identity, skills, and noble character following the guidance of Prophet Muhammad Shalallahu ‘alaihi wasallam.